Diffusion of Schwiebea (Jacotietta) codognoensis Fain & Pagani in drinking-water of a small town in northern Italy. (Bollettino di zoologia agraria e bachicoltura, 2024)
lt have been investigated on the possibility of correlations between populations of Acari, Copepoda, Nematoda and Rotifera living in drinking-water of waterworks. The statistical analysis of the available data can't give sure results. However they seem to point out connection between organisms to examine closely.
Keywords: aqueducts; ecology; invertebrates; mites; Schwiebea